A Point-to-Point Interference Measurement Approach for Large-Scale Wireless Sensor Networks. (22nd October 2012) - Zeng, Bo; Dong, Yabo; Lu, Dongming
Abstract : Interference measurement is an important part for use in links scheduling protocol in wireless sensor networks (WSNs). To know wireless interference among nodes in the network is essential to guarantee the efficiency of links scheduling protocol. This work presents a point-to-point interference measurement approach based on time division technique for large-scale low-power WSNs. We first propose an optimized time-slots assignment to reduce the time-slot requirement of interference measurement for large-scale WSNs.We then mitigate the problem of communication by using a subtree-based information distribution method. The accuracy of interference measurement is controlled by a control factor that can be specified by user based on the application requirement to achieve a tradeoff between the overhead of measuring interference and measurement accuracy. Our simulation results indicate that our approach has low-energy and-communication overhead when compared with baseline.